The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1139/cjz-2013-0223
|View full text |Cite
|
Sign up to set email alerts
|

Critical thermal maximum (CTmax) and hematology of shortnose sturgeons (Acipenser brevirostrum) acclimated to three temperatures

Abstract: Quantifying a species thermal tolerance is critical to assessing biological impacts of anticipated increases in temperature (e.g., climate change). Although many studies have documented the critical thermal maximum (CT max ) of fish, there is a paucity of research on thermal biology of sturgeon. The shortnose sturgeon (Acipenser brevirostrum LeSueur, 1818) is a threatened species that exists along the eastern coast of North America. They can be exposed to temperatures ranging from freezing to above 25°C. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 34 publications
12
61
1
Order By: Relevance
“…This is perplexing since most sturgeon species are protected under legislation due to human‐made disturbances that might involve water temperature alterations (Pikitch et al., ). The critical thermal maximum values for Atlantic and shortnose sturgeon noted in the present study were found to be similar to those in other studies using pallid ( Scaphirhynchus albus ), Lake ( Acipenser fulvescens ), shortnose, shovelnose ( Scaphirhynchus platorynchus ) and green ( Acipenser medirostris ) sturgeons (Sardella et al., ; Zhang and Kieffer, ; D. Deslauriers, unpubl. data; Table ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is perplexing since most sturgeon species are protected under legislation due to human‐made disturbances that might involve water temperature alterations (Pikitch et al., ). The critical thermal maximum values for Atlantic and shortnose sturgeon noted in the present study were found to be similar to those in other studies using pallid ( Scaphirhynchus albus ), Lake ( Acipenser fulvescens ), shortnose, shovelnose ( Scaphirhynchus platorynchus ) and green ( Acipenser medirostris ) sturgeons (Sardella et al., ; Zhang and Kieffer, ; D. Deslauriers, unpubl. data; Table ).…”
Section: Discussionsupporting
confidence: 91%
“…CTmax led to a marked change in a number of blood parameters across sturgeon species, which is indicative of increased stress in the animal (Wedemeyer et al., ; Barton et al., ). Lactate concentrations increased in Atlantic and shortnose sturgeon during the thermal stress and at levels comparable to previous research on shortnose sturgeon (Zhang and Kieffer, ; Y. Zhang and J. D. Kieffer, unpubl. data).…”
Section: Discussionsupporting
confidence: 88%
“…The adoption of the CTM parameter allowed researchers to evaluate the thermal tolerance of different organisms (Cowles and Bogert, 1944; Lutterschmidt and Hutchison, 1997; Zhang and Kieffer, 2014). Limnic planarians exposed to the CTM, show signs of contortions, sluggishness, and an injured epidermis, losing their ability to move properly before dying (Claussen and Walters, 1982; Tsukuda and Ogoshi, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In nature, a loss of equilibrium affects an organism's ability to forage or avoid predation, which may ultimately affect individual fitness. As acclimation temperature ( T a ) has been found to be correlated positively with CT max (Cox et al ., 1974; Zhang and Kieffer, 2014; McDonnell and Chapman, 2015, although see Galbreath et al ., 2004; Recsetar et al ., 2012), the ancestral history and origin of a population are thought to be linked to an organism's ability to tolerate temperature increases (Stockwell et al ., 2003; McDermid et al ., 2012) and, as such, stream temperature regimes may result in population-specific thermal tolerance. A relatively new metric to assess thermal tolerance, agitation temperature, described by McDonnell and Chapman (2015) as the temperature at which a fish first begins to exhibit refugia-seeking behaviour (circling of the chamber, seeking refuge in substrate), may also provide insight to how quickly individuals can sense and attempt to react to environmental change.…”
Section: Introductionmentioning
confidence: 99%